2y+3(y-4)=2(y-3)

Simple and best practice solution for 2y+3(y-4)=2(y-3) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 2y+3(y-4)=2(y-3) equation:


Simplifying
2y + 3(y + -4) = 2(y + -3)

Reorder the terms:
2y + 3(-4 + y) = 2(y + -3)
2y + (-4 * 3 + y * 3) = 2(y + -3)
2y + (-12 + 3y) = 2(y + -3)

Reorder the terms:
-12 + 2y + 3y = 2(y + -3)

Combine like terms: 2y + 3y = 5y
-12 + 5y = 2(y + -3)

Reorder the terms:
-12 + 5y = 2(-3 + y)
-12 + 5y = (-3 * 2 + y * 2)
-12 + 5y = (-6 + 2y)

Solving
-12 + 5y = -6 + 2y

Solving for variable 'y'.

Move all terms containing y to the left, all other terms to the right.

Add '-2y' to each side of the equation.
-12 + 5y + -2y = -6 + 2y + -2y

Combine like terms: 5y + -2y = 3y
-12 + 3y = -6 + 2y + -2y

Combine like terms: 2y + -2y = 0
-12 + 3y = -6 + 0
-12 + 3y = -6

Add '12' to each side of the equation.
-12 + 12 + 3y = -6 + 12

Combine like terms: -12 + 12 = 0
0 + 3y = -6 + 12
3y = -6 + 12

Combine like terms: -6 + 12 = 6
3y = 6

Divide each side by '3'.
y = 2

Simplifying
y = 2

See similar equations:

| f/4=4 | | t/8=2 | | 14=(0)t+(0.5)(9.8)t^2 | | -3x+5y=-33 | | 20+4H=32 | | 3x-1+10x^2= | | -n+7(n-4)=-2(5n-2) | | x^3+7x^2+2x=0 | | -x^2+x+56=0 | | 40+14j=2(-4j+-13) | | -6h+2h-11=-2(2h-3)+4 | | x=.5(3+7)4 | | p/5=6 | | -6x+3y=-30 | | -37+2m=-7(-m+1) | | -x^2+21+x=0 | | -5+2x=-1 | | 2n-6=-24 | | 28x^2-37x-21= | | 3(4c+1)-17=2(3c+2)-3c | | 5=7x-2 | | (7.29)(0.6+0.7)= | | 3(2x+1)=5 | | 7x-5y=-19 | | -3x+6=-27 | | y=0.3-2 | | (3w+5)(3w-5)= | | .5x+.40(400)=.10(x+400) | | 2x(-10)+y(-11)=180 | | -3x+6=-24 | | .5x+.30(400)=.10(x+400) | | -5x+8=-7 |

Equations solver categories